Kandungan Nutrisi dan Bioaktif Rumput Laut (Euchema cottonii) dengan Metode Rakit Gantung pada Kedalaman Berbeda: Nutrition and Bioactive Compound of Seaweed (Euchema cottonii) with Hanging Raft Method at Different Depths - Safia, Waode; Budiyanti; Musrif (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Many manufacture industries such as food, cosmetic, pharmaceutical, textile and agricultural industries utilize raw materials derived from seaweed. Agar, carrageenan, and alginate are often used as stabilizers, manufacturing materials, forming gels and emulsifiers. The nutrient levels and bioactive compounds in seaweeds are generally different depends on species, handling, culture period, and the culture location. This research was aimed to determine the depth of seaweed (Eucheuma cottonii) raft resulting in high nutrient content and bioactive compounds. Three groups were evaluated: Group I (from coastline to the lowest tidal); Group II (100 m from the lowest tidal) and group III (100 m away from group II). E. cottonii rafts were built in each group at 0.5 m, 1 m, and 2 m deep. Nutrient content including protein, lipid, and carbohydrate levels as well as bioactive compounds were determined. The highest nutrient content was found in seaweed growth in the 1 m deep hanging raft with protein of 4.16±0.61%, lipid 0.36±0.23%, and carbohydrate 25,50±6.06%. Phytochemical compounds including flavonoids, phenols hydroquinone, and tannins were identified in seaweed at all depths.